SEMIOTIKA ROLAND BARTHES DALAM IKLAN RINSO ‘YUK MULAI BIJAK PLASTIK!’ - Mukhsin Patriansah; Ria Sapitri; Didiek Prasetya (Narada : Jurnal Desain dan Seni, 2022)
The problem of plastic waste is a very complicated problem faced by this nation, the low level of public awareness in using and managing plastic waste is the main trigger for natural and environmental damage. Nature is a very good playground for children, they can freely explore. If nature is not maintained then the next generation can no longer feel the beauty of nature. Realizing this problem, Rinso campaigned for a 'Let's Start Wise Plastic' campaign in collaboration with Word Clean-up Day (WCD) as a real step to invite the public to increase their awareness of the problem of plastic waste. The study of verbal and visual messages in this study, the author uses Roland Barthes' Semiotic theory which aims to see the coding system and layers of denotative and connotative signs in Rinso's advertising campaign 'Yuk Start Bijak Plastik'.